ASSOCIATION OF RISK FACTORS FOR CHOROIDAL NEOVASCULARIZATION IN AMD WITH DECREASED FOVEOLAR CHOROIDAL CIRCULATION - Xu, Wei (2010)
PURPOSE: To investigate the relationship between known risk factors for Age-related macular degeneration (AMD) progression and foveolar choroidal circulation in eyes with non-exudative AMD. DESIGN: A cross-sectional study in non-exudative AMD. METHODS: Laser Doppler Flowmetry (LDF) measurements of relative choroidal blood velocity (ChBVel), volume (ChBVol) and flow (ChBFlow) were obtained in the center of the fovea of 273 study eyes of 204 AMD patients investigated at the Scheie Eye Institute of the University of Pennsylvania Medical School. All study eyes had visual acuity of 20/40 or better, good fixation, no other intraocular pathology and no evidence of choroidal neovascularization. RPE hypertrophy was determined from color fundus photographs by trained masked graders at the Scheie Image Reading Center. Correlation analysis and multivariate linear regression analysis with adjustments for significant covariates were carried out. RESULTS: A significant inverse correlation was observed between age and ChBFlow (r=− 0.36, p<0.0001), and ChBVol (r=−0.28, p<0.0001), but not for ChBVel. A significant inverse correlation was observed between spherical equivalent and ChBFlow (r=−0.21, p=0.006), and ChBVol (r=−0.14, p=0.04) but not for ChBVel. ChBFlow and ChBVol were significantly lower in patients with a history of hypertension (p≤0.003) and in eyes with RPE hypertrophy (p≤0.04), respectively. CONCLUSIONS: All the above described risk factors for AMD development and progression are associated with decreased choroidal circulatory parameters, suggesting that decreases in choroidal circulatory parameters may be involved in the development of AMD.